Pancreatic foregut cystic malformation with a bifid pancreatic tail - Yuki Endo; Motoshi Wada; Hideyuki Sasaki; Taichi Fukuzawa; Hironori Kudo; Ryo Ando; Satoshi Yamaki; Ryuji Okubo; Masatoshi Hashimoto; Yudai Nakajima; Kosuke Sato; Hidekazu Aoki; et al. (Elsevier, 2021)
A two-year-old girl presented with an abdominal mass, abdominal pain, and fever. A quail egg-sized elastic-hard mass was palpable in the upper left abdomen. The patient's growth was impaired. Laboratory data showed an inflammatory response and elevated pancreatic enzymes. The mass showed a cystic structure adjacent to the caudal side of the bifid tail of the pancreas. A fluid collection was observed around the spleen. Surgery was planned under the diagnosis of pancreatic foregut cystic malformation (FCM) associated with a bifid pancreatic tail. However, as the inflammation worsened, parenteral nutrition (PN) was introduced and cyst drainage was performed first, obtaining 10-14 mL/day, and her symptoms subsided. Cyst drainage continued for six weeks at home. Laparoscopic surgery was performed 47 days after the initiation of drainage. Cystography showed communication between the cyst and the slightly dilated pancreatic duct of the bifid tail during surgery. A partial pancreatectomy with cystectomy was performed. The diagnosis of FCM originating from the pancreas, associated with the bifid tail, was confirmed. The postoperative course was uneventful, and the patient was discharged eight days post-surgery. Pancreatic FCM with a bifid pancreatic tail is rare, and we successfully treated it using minimally invasive surgery.